ADAPTIVE EFFORTS AND IMPLEMENTATION OF THE PENAHELIX MODEL IN THE DEVELOPMENT AND SUSTAINABILITY OF MSMEs IN PENGLATAN VILLAGE DURING THE SARS COV-2 PANDEMIC. - Putu Eka Dianita Marvilianti Dewi; Sunitha Devi; Putu Riesty Masdiantini (Jurnal Ilmiah Akuntansi dan Humanika, 2023)
The decline in the productivity level of MSMEs is caused by the global impact of the Covid-19 pandemic, the MSME sector most affected is MSME engaged in the food industry. The purpose of this mini research is to examine how the adaptive efforts and implementation of the pentahelix model are carried out by MSME engaged in the food industry in Penglatan Village to survive and develop businesses sustainably in the midst of a pandemic situation. The research method used is descriptive qualitative method by conducting separate interviews with MSME owners. This study uses the concept of the pentahelix model with the results of the analysis of adaptive efforts and the implementation of the pentahelix model. MSMEs that are able to survive and are still producing in the midst of a pandemic make various efforts that are adapted to the situation and market demand, adaptations made by several MSMEs are starting to sell by utilizing information technology and selling and promoting products online.